2020
DOI: 10.35759/janmplsci.v46-2.6
|View full text |Cite
|
Sign up to set email alerts
|

Caractérisation et typologie des systèmes d’élevage de la poule locale du Burkina Faso

Abstract: La présente étude est une contribution à l’établissement des caractéristiques et de la typologie des systèmes d’élevage de la poule locale dans les 3 zones agro écologique du Burkina Faso. Des informations ont été collectées sur 251 éleveurs de poules locales à travers une enquête de type transversale dans les 3 zones agro-écologiques, du Burkina Faso. Les résultats indiquent que l’élevage des poules locales est pratiqué principalement par des autochtones (84,91%) et des hommes (70,26%) dans un système extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 1 publication
5
5
2
Order By: Relevance
“…The typological analysis allowed us to meet one of the objectives of this study, which is to classify traditional poultry breeding farms according to the values of the synthetic variables taken into account in the classification and the significant links established between the groups of individuals. The results of the present study differ from those obtained by Dzogbema et al (2021), andPindé et al (2020) in Togo, and Burkina Faso with regard to the objectives of the study and the variables introduced for the analysis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The typological analysis allowed us to meet one of the objectives of this study, which is to classify traditional poultry breeding farms according to the values of the synthetic variables taken into account in the classification and the significant links established between the groups of individuals. The results of the present study differ from those obtained by Dzogbema et al (2021), andPindé et al (2020) in Togo, and Burkina Faso with regard to the objectives of the study and the variables introduced for the analysis.…”
Section: Discussioncontrasting
confidence: 99%
“…This trend was previously reported in the results of the General Census of Agriculture and Livestock (RGAC, 2008), indicating that poultry breeding in Niger is practiced by 48% of men, 28% of children, and 24% of women. The findings of the current study are in agreement with the study conducted in Burkina Faso, where Pindé et al (2020) reported that 70.26% of men practiced poultry farming. Conversely, a Zimbabwean study revealed that 88.9% of women dominated poultry activities (Ndiweni et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…They had all poultry farming as their main activity with an average of 12 ± 5.50 years of experience, only 5% practiced agriculture in addition to poultry activity. These results differ from those obtained by Pindé et al (2020). Indeed, these authors obtained that 27% practiced poultry farming compared to 67% who practiced agriculture in their study.…”
Section: Socio-economic Aspectscontrasting
confidence: 91%
“…These introduced chickens have certainly contributed to the dilution of the genetic diversity in local chicken populations and could pose a threat to the existing genetic variability. Local chicken farming in Burkina Faso, as in many developing countries, plays an important role among small-scale producers as the major source of animal protein to humans, income and socio-cultural role [ 3 , 4 , 5 , 6 ]. However, in Burkina Faso, studies of the genetic diversity of local chicken populations are scarce and often limited to the morpho-biometric characteristics of these populations [ 7 , 8 ] and to farm typologies [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Local chicken farming in Burkina Faso, as in many developing countries, plays an important role among small-scale producers as the major source of animal protein to humans, income and socio-cultural role [ 3 , 4 , 5 , 6 ]. However, in Burkina Faso, studies of the genetic diversity of local chicken populations are scarce and often limited to the morpho-biometric characteristics of these populations [ 7 , 8 ] and to farm typologies [ 6 ]. To date, there is no relevant information on the genetic diversity and genetic structure of local chicken population in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%